Review of The Many Histories of Naqada: Archaeology and Heritage in an Upper Egyptian Region - Brémont, Axelle.
Alice Stevenson & Joris van Wetering (eds.), The Many Histories of Naqada: Archaeology and Heritage in an Upper Egyptian Region. London: Golden House Publications, 2020. ISBN 9781906137694. Pp. Xviii + 171, 160 black and white illustrations.